Molecular Mobility in Hyperbranched Polymers and Their Interaction with an Epoxy Matrix - Román, Frida (Materials (Basel), 2016)
The molecular mobility related to the glass transition and secondary relaxations in a hyperbranched polyethyleneimine, HBPEI, and its relaxation behaviour when incorporated into an epoxy resin matrix are investigated by dielectric relaxation spectroscopy (DRS) and dynamic mechanical analysis (DMA). Three systems are analysed: HBPEI, epoxy and an epoxy/HBPEI mixture, denoted ELP. The DRS behaviour is monitored in the ELP system in three stages: prior to curing, during curing, and in the fully cured system. In the stage prior to curing, DRS measurements show three dipolar relaxations: γ, β and α, for all systems (HBPEI, epoxy and ELP). The α-relaxation for the ELP system deviates significantly from that for HBPEI, but superposes on that for the epoxy resin. The fully cured thermoset displays both β- and α-relaxations. In DMA measurements, both α- and β-relaxations are observed in all systems and in both the uncured and fully cured systems, similar to the behaviour identified by DRS.